"A Highland Thing": Heavy Metal and the Construction of Cultural Difference in Madagascar. (19th April 2017) - Verne, Markus
Abstract : Around the mid-1980s, when Madagascar's socialist "Second Republic" effectively came to an end, a small but significant heavy metal community evolved in the island's capital, Antananarivo. While interest in this kind of music declined during the 1990s, echoing developments within global popular music, Malagasy metal never ceased to exist and, during the last ten years,  enjoyed renewed popularity. This popularity has, however, always been restricted to Madagascar's central highlands, which rendered Malagasy metal "a highland thing" in the eyes of both highland and coastal populations. It is because of this regionalized perception, I will argue in this article, that Malagasy heavy metal considerably contributes to the maintenance of a fundamental cultural divide that separates Madagascar's highlands from its coastal populations,  thereby undermining political struggles aiming at the creation of a shared national identity.